FGFR4 Gly388Arg Polymorphism Reveals a Poor Prognosis, Especially in Asian Cancer Patients: A Meta-Analysis - Kim, Jung Han; Jeong, Soo Young; Jang, Hyun Joo; Park, Sung Taek; Kim, Hyeong Su (Frontiers in Oncology, 2021)
The fibroblast growth factor-4 receptor (FGFR4) is a member of receptor tyrosine kinase. The FGFR4 Gly388Arg polymorphism in the transmembrane domain of the receptor has been shown to increase genetic susceptibility to cancers. However, its prognostic impact in cancer patients still remains controversial. Herein, we performed this meta-analysis to evaluate the clinicopathological and prognostic impacts of the FGFR4 Gly388Arg polymorphism in patients with cancer. We carried out a computerized extensive search using PubMed, Medline, and Ovid Medline databases up to July 2021. From 44 studies, 11,574 patients were included in the current meta-analysis. Regardless of the genetic models, there was no significant correlation of the FGFR4 Gly388Arg polymorphism with disease stage 3/4. In the homozygous model (Arg/Arg vs. Gly/Gly), the Arg/Arg genotype tended to show higher rate of lymph node metastasis compared with the Gly/Gly genotype (odds ratio = 1.21, 95% confidence interval (CI): 0.99-1.49, p = 0.06). Compared to patients with the Arg/Gly or Arg/Arg genotype, those with the Gly/Gly genotype had significantly better overall survival (hazard ratios (HR) = 1.19, 95% CI: 1.05-1.35, p = 0.006) and disease-free survival (HR = 1.25, 95% CI: 1.03-1.53, p = 0.02). In conclusion, this meta-analysis showed that the FGFR4 Gly388Arg polymorphism was significantly associated with worse prognosis in cancer patients. Our results suggest that this polymorphism may be a valuable genetic marker to identify patients at higher risk of recurrence or mortality.